Bridgman Development of GaSe Crystals for Nonlinear Optic Uses - Nguyen Thi Phuong Loan; Hsiao-Yi Lee; Aditya Sripathi Bharadwaj; Gaurav Kumar Bharti (Indonesian Journal of Material Research, 2026)
We report the growth and fabrication of high-quality GaSe single crystals tailored for uses of nonlinear optics in the mid-infrared spectral range. To improve crystal uniformity and nonlinear performance, the temperature distribution of the crystal-growth furnace was optimized using a computational model based on the finite-volume method, enabling precise control of thermal gradients during solidification. Vertical crystal development was subsequently carried out using the liquid-encapsulated Bridgman technique, which minimizes melt oxidation and promotes stable crystallization. GaSe crystals produced under the optimized furnace temperature profile exhibited significantly enhanced nonlinear optical behavior, with a higher second-harmonic conversion coefficient (d) compared with conventionally grown, undoped GaSe crystals. These results demonstrate that furnace-design optimization is an effective strategy for improving the nonlinear optical efficiency of GaSe, making the material more suitable for advanced mid-IR frequency-conversion devices.